Analisis Pengaruh Dimensi Budaya Organisasi dan Iklim Organisasi terhadap Kinerja Pegawai pada Satuan Polisi Pamong Praja Kota Pontianak - Indah Astuti; Yusmainiar Yusmainiar (Jurnal Ilmiah Aset, 2019)
The company’s ability to adapt and change in memanajemeni is one of the company’s actions in winning the competition. One of the keys to success in the management of such changes is the existence of organizational culture and organizational climate. Police units of teachers ‘ Praja Pontianak town is one of the Government organizations that helped organise the governance and development in the city of Pontianak. For it was then the Police Unit of teachers ‘ Praja Pontianak town should pay attention to how management practices through the application of organizational culture and organizational climate are internal in order to build a good performance for each employee. Therefore it is necessary to do an analysis of organizational culture and organizational climate on performance on a unit of Police teachers ‘ Praja Pontianak town. Problems in the study is how the influence of the dimensions of organizational culture and organizational climate on performance clerk Police teachers ‘ Praja Pontianak town? Samples done by stratified random sampling. Of the total population of 110 people taken 30% or as much as 34 people taken into the sample. Analysis for discussion of using Multiple Regression. Simultaneous test results it can be concluded that the variables of organizational climate and organizational culture has a real influence on performance of respondents on a unit of Police teachers ‘ Praja Pontianak town. From the analysis of partially can be concluded that the organizational culture and organizational climate has a real influence on performance of respondents on a unit of Police teachers ‘ Praja Pontianak town.